Effectiveness of acupuncture therapy Li point 4 (Hegu), Lu 7 (Lieque) and facial massage in reducing scale wrinkles in Dangkrang, Purwantoro, Wonogiri environments - Pebriani, Nur Indah; Badri, Solichan (HAKTI : Indonesian Acupuncture Therapists Association, 2024)
Wrinkles on the face are one of the processes of aging factors. The thinning of the collagen and elastin layers on the skin causes facial wrinkles. The wrinkles are due to a lack of thickness of the dermis layer of as much as 20%, which is associated with the loss of elastin and collagen fibers. This study uses the pre-experimental design with the pretest-posttest control group design method. The research was conducted from October 2018 to April 2019 in Dangkrang Environment, Purwantoro, Wonogiri. The study used a sample of 40 subjects meeting the inclusion and exclusion criteria divided into two groups (n = 20). Group I was treated with point acupuncture therapy LI 4 (Hegu), LU 7 (Lieque), and face massage.The Mann-Whitney U Test statistics obtained a p-value of 0.001. The results showed significant differences in changes in the face area between the two groups. Point acupuncture therapy LI 4 (Hegu), LU 7 (Lieque), and facial massage are more effective in reducing the scale of wrinkles on the face in the Dangkrang, Purwantoro, Wonogiri surroundings.